Electrical impedance tomography for damage detection and localization on carbon fibre reinforced polymer composites - Rocha, Helena Cristina Lopes (2022)
Electrical impedance tomography (EIT) is being developed as promising non-intrusive technology for damage detection in conductive fibre reinforced polymers (FRP) composites. This work assessed EIT and one-step difference Gaussian-Newton algorithm to detect different damages in CFRP laminates, including through-thickness holes and impact damage of different severities. Two layup laminates were studied: quasi-isotropic [0/45/90/-45]s and unbalanced [0/0/45/90/-45]s. Each laminate configuration was subjected to three levels of impact energy.Through-thickness holes with diameters as small as 2 mm were detected. The LVI on unbalanced specimens created elongated shaped damages, which were observed through EIT and ultrasonic C-scan. Differently, the ultrasonic C-scan inspections revealed circular shaped damages on the centre of the quasi-isotropic specimens, while EIT could not reveal a well-defined damage shape Yet, the presence of damage was observed in the centre of the specimens by EIT. Although EIT overestimated the damaged area, it was highly sensitive to the imposed damages.